Innate Immune Regulations and Liver Ischemia-Reperfusion Injury. Issue 12 (December 2016) - Lu, Ling; Zhou, Haoming; Ni, Ming; Wang, Xuehao; Busuttil, Ronald; Kupiec-Weglinski, Jerzy; Zhai, Yuan
Abstract : Abstract: Liver ischemia reperfusion activates innate immune system to drive the full development of inflammatory hepatocellular injury. Damage-associated molecular patterns (DAMPs) stimulate myeloid and dendritic cells via pattern recognition receptors (PRRs) to initiate the immune response. Complex intracellular signaling network transduces inflammatory signaling to regulate both innate immune cell activation and parenchymal cell death. Recent studies have revealed that DAMPs may trigger not only proinflammatory but also immune regulatory responses by activating different PRRs or distinctive intracellular signaling pathways or in special cell populations. Additionally, tissue injury milieu activates PRR-independent receptors which also regulate inflammatory disease processes. Thus, the innate immune mechanism of liver ischemia-reperfusion injury involves diverse molecular and cellular interactions, subjected to both endogenous and exogenous regulation in different cells. A better understanding of these complicated regulatory pathways/network is imperative for us in designing safe and effective therapeutic strategy to ameliorate liver ischemia-reperfusion injury in patients. Abstract : The authors summarize the mechanism of hepatic ischemia reperfusion injury on the activation of innate immune system and the regulatory pathways/network of liver graft injury.